Detectability of hepatocellular carcinoma on gadoxetic acid-enhanced MRI at 3 T in patients with severe liver dysfunction: clinical impact of dual-source parallel radiofrequency excitation. Issue 3 (March 2015) - Nishie, A.; Kakihara, D.; Asayama, Y.; Ushijima, Y.; Takayama, Y.; Fujita, N.; Shimamoto, D.; Shirabe, K.; Hida, T.; Honda, H.
Abstract Aim To clarify the detectability of hepatocellular carcinoma (HCC) on gadoxetic acid-enhanced MRI at 3 T with dual-source parallel radiofrequency (RF) excitation. Materials and methods Twelve patients with 26 HCCs who each underwent multidetector row CT (MDCT), gadoxetic acid-enhanced MRI with dual-source parallel RF excitation, and angiography-assisted CT prior to living related-liver transplantation. Three blinded readers independently reviewed the images obtained by each imaging technique for the presence of HCC on a segment-by-segment basis using a five-point confidence scale. The area under the receiver operating characteristic curve (Az), sensitivity, and specificity were compared among the three techniques. Results The Az values of gadoxetic acid-enhanced MRI were highest for all readers, although no significant difference in Az value among the three methods was obtained. No significant differences in sensitivity or specificity were observed among the three techniques for each reader. Conclusion Gadoxetic acid-enhanced MRI at 3 T with dual-source parallel RF excitation has relatively high-level diagnostic potential for the detection of HCC in patients with severe liver dysfunction, which was equivalent to that of MDCT and angiography-assisted CT. Dual-source parallel RF excitation would have a clinical impact on 3 T MRI of the liver.